2022
DOI: 10.3389/fmicb.2022.897387
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Mechanism of Lactiplantibacillus plantarum KM1 Under H2O2 Stress by Proteomics Analysis

Abstract: Lactiplantibacillus plantarum KM1 was screened from natural fermented products, which had probiotic properties and antioxidant function. The survival rate of L. plantarum KM1 was 78.26% at 5 mM H2O2. In this study, the antioxidant mechanism of L. plantarum KM1 was deeply analyzed by using the proteomics method. The results demonstrated that a total of 112 differentially expressed proteins (DEPs) were screened, of which, 31 DEPs were upregulated and 81 were downregulated. The Kyoto Encyclopedia of Genes and Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Importantly, the TGs buildup in hepatocytes was previously linked with insulin resistance, putting the liver at risk of additional damage [ 57 ]. Additionally, alloxan induces the liver’s conversion of fatty acids to cholesterol and increases triglyceride formation, released into the bloodstream as lipoproteins [ 58 ]. Hence, the liver’s stellate cells may be stimulated by oxidative stress and steatohepatitis, which are detected in this study, leading to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the TGs buildup in hepatocytes was previously linked with insulin resistance, putting the liver at risk of additional damage [ 57 ]. Additionally, alloxan induces the liver’s conversion of fatty acids to cholesterol and increases triglyceride formation, released into the bloodstream as lipoproteins [ 58 ]. Hence, the liver’s stellate cells may be stimulated by oxidative stress and steatohepatitis, which are detected in this study, leading to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some researchers have used omics studies to reveal the molecular mechanism of the antioxidant performance of L. plantarum. The results showed that various metabolic pathways such as base excision repair system, recombinational DNA repair pathway, pyruvate metabolism, carbon metabolism, trichloroacetic acid cycle, amino acid metabolism, and microbial metabolism were closely related to these antioxidant properties ( Zhai et al, 2020 ; Tian et al, 2022 ). In future studies, we can use these methods to further explore the molecular mechanism of GXL94 antioxidant properties.…”
Section: Discussionmentioning
confidence: 99%